CORPORATE GOVERNANCE SEBAGAI PEMODERASI PENGARUH ASIMETRI INFORMASI TERHADAP PRAKTIK MANAJEMEN LABA - Anggreningsih, Kadek Yulika; Wirasedana, I Wayan Pradnyantha (E-Jurnal Akuntansi; Vol 19 No 3 (2017), 2017)
The application of good corporate governance in a company expected to reduce the asymmetry of information that is often experienced by shareholders who can then open the possibility of earnings management practices conducted by the management in order to achieve personal goals. This study aims to determine the effect of information asymmetry on earnings management practices in corporate governance as moderating variables. The study was conducted at the manufacturing companies listed in Indonesia Stock Exchange in 2013-2015. The research sample obtained 85 by purposive sampling method. Data analysis techniques used are moderated regression analysis. The analysis finds that the information asymmetry significant negative effect on earnings management practices and corporate governance by proxy management ownership weaken the influence of asymmetry of information on earnings management practices, institutional ownership and audit committee was not able to moderate, and independent commissioner strengthen the influence asymmetry of information on earnings management practices.
Keywords: Earnings Management, Information Asymmetry, Corporate Governance